Bartonella-like bacteria carried by domestic mite species - Kopecký, Jan; Nesvorná, Marta; Hubert, Jan (Experimental & applied acarology, 2014)
Bacteria of the genus Bartonella are carried by haematophagous mites, ticks, fleas and flies, and attack the erythrocytes of mammals. Here we describe a Bartonella-like clade, a distinct group related to Bartonellaceae, in stored-product mites (Acari: Astigmata) and a predatory mite Cheyletus eruditus (Acari: Prostigmata) based on the analysis of cloned 16S rRNA gene sequences. By using the clade-specific primers, closely related Bartonella-like 16S rRNA sequences were amplified from both laboratory colonies and field strains of three synanthropic mite species (Acarus siro, Lepidoglyphus destructor and Tyrophagus putrescentiae) and a predatory mite. Altogether, sequences of Bartonella-like bacteria were found in 11 strains, but were not detected in Dermatophagoides farinae and D. pteronyssinus and two strains of L. destructor. All obtained sequences formed a separate cluster branching as a sister group to Bartonellaceae and related to other separate clusters comprising uncultured bacterial clones from human skin and hemipteran insects (Nysius plebeius and Nysius sp.). The classification of sequences into operational taxonomic units (OTUs) showed a difference between A. siro and T. putrescentiae suggesting that the Bartonella-like bacteria are different in these two mite species. However, species specific sequences in separate OTUs were observed also for C. eruditus. Possible symbiotic interactions between Bartonella-like bacteria and their mite hosts are discussed.
Keywords: Animals; Phylogeny; symbióza; zvířata; fylogeneze; Symbiosis; roztoči; Bartonella; Mites